Profil umum dermatitis kontak akibat kerja pada pegawai salon di wilayah Denpasar Selatan - Made Dalika Nareswari; I Gusti Ayu Agung Elis Indira (Universitas Udayana, 2018)
Contact dermatitis is a condition in which the skin become inflamed due to external factors as well as the surrounding environment or the substances that interact with the skin. Occupational contact dermatitis can occur in the salon workers which generally arises due to exposure to water and chemicals in the long term and repetitive. The purpose of this study was to determine the general profile of occupational contact dermatitis on salon employees in the South Denpasar. This research is an observational study using cross-sectional descriptive approach. Samples were salon employees who are in the South Denpasar and suffer or have ever suffered from contact dermatitis. The sampling technique using total sampling. The research was conducted from March to September in 2016. The instrument used in this study was a questionnaire. The result showed 45 samples with 22 people (48.9%) experience contact dermatitis during work and 23 people (51.1%) did not experience contact dermatitis, long working perday most obtained at ? 10 hours groups with 22 people (48.9%), the frequency of exposure to the most widely found in the group of ? 5 times with 28 people (62.2%), the most widely performed work that is smoothing-curly-hair rebonding which is done by 30 people (66.7%). It can be concluded that the picture of the incidence of contact dermatitis due to work at the salon workers have almost the same distribution. This study is expected to be deepened with better methods and use of investigation to assist in diagnosis. Keywords: occupational contact dermatitis, employee salon, cross-sectional